Teṉṉāprikka Intiyar pōrāṭṭam - Māricāmi, Es. Es., 1920- (SAMP early 20th-century Indian books project ;, 1947)
On the struggle of Indians in South Africa and the role of Mahatma Gandhi, 1869-1948, Indian statesman.